2008
DOI: 10.1123/jsep.30.6.685
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Structured Activity and Deliberate Play to the Development of Expert Perceptual and Decision-Making Skill

Abstract: The developmental histories of 32 players in the Australian Football League (AFL), independently classified as either expert or less skilled in their perceptual and decision-making skills, were collected through a structured interview process and their year-on-year involvement in structured and deliberate play activities retrospectively determined. Despite being drawn from the same elite level of competition, the expert decision-makers differed from the less skilled in having accrued, during their developing y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
140
1
11

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(166 citation statements)
references
References 35 publications
14
140
1
11
Order By: Relevance
“…Players participated in a mean number of two other sports during childhood, which they mainly started participating in at secondary school age (mean start age 11 years). This finding contradicts the previous research of Berry et al (2008) who showed that engaging in other related sports is associated to better decision making in the primary sport. We speculate that the skilled high-performing group was following the ''early engagement'' pathway proposed by Ford et al (2009).…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Players participated in a mean number of two other sports during childhood, which they mainly started participating in at secondary school age (mean start age 11 years). This finding contradicts the previous research of Berry et al (2008) who showed that engaging in other related sports is associated to better decision making in the primary sport. We speculate that the skilled high-performing group was following the ''early engagement'' pathway proposed by Ford et al (2009).…”
Section: Discussioncontrasting
confidence: 57%
“…Moreover, it is likely that hours accumulated in total soccer activity by 18 years of age will differentiate skill groups (cf., Ford et al, 2010a). We assumed that the development of anticipation and decision making in soccer is mainly a result of participation in the primary sport, rather than engagement in other sports per se (e.g., Berry et al, 2008), due to the low number of other sports engaged in by soccer players during their development (e.g., Ford et al, 2009;Ward et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such related bodies of literature concerning talent identification and expert performance in elite sport (Abernethy, 1991;Allard, 1993;Baker, Cote, & Abernethy, 2003;Berry, Abernethy, & Côté, 2008;Raab et al, 2005;Starkes & Ericsson, 2003; among others) and within the research area of motor development in young children, giving considerable attention to how the development of TAP occurs (Haywood & Getchell, 2009;Thomas et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Neste âmbito, a investigação tem claramente demonstrado a importância da quantidade e do tipo de prática enquanto poderosas influências no desenvolvimento do atleta e, consequentemente, da excelência no desporto (7,15,17,23,31) .…”
unclassified